Prognostic importance of tumour-infiltrating memory T cells in oesophageal squamous cell carcinoma - Enomoto, K (Blackwell Publishing Ltd, 2012)
Memory T cells survive for many months and years and are critically important for host defence in humans. In tumour immunity, they have been also suggested to play a significant role in tumour progression and metastasis. However, the role of memory T cells in actual human cancer remains largely unknown. In this study, the clinical importance of tumour-infiltrating CD45RO(+) memory T cells was investigated in human oesophageal squamous cell carcinoma (OSCC). CD45RO(+) T cells were evaluated by immunohistochemistry in primary OSCC tumours from 105 patients. Patients were classified into two groups as CD45RO(+hi) or CD45RO(+lo) based on the number of cells stained positively for CD45RO. No significant difference was observed between CD45RO status and several clinicopathological prognostic factors. However, the postoperative overall and disease-free survival for CD45RO(+hi) patients was significantly better than for CD45RO(+lo) patients. Furthermore, there were significant correlations of CD45RO status in the primary tumour with postoperative lymph node and pulmonary recurrence, suggesting that memory T cells may control postoperative metastatic recurrence. Most importantly, CD45RO(+) memory T cell status has a significant prognostic value for OSCC independently of conventional tumour–node–metastasis (TNM) classification. Our study may provide a rationale for developing a novel immunotherapy in intentional induction of memory T cells for the treatment of oesophageal cancer.